Beach Erosion Impact In Manggopoh Palak Gadang Ulakan Village (JURNAL SPASIAL, 2019)
Beach erosion is an unavoidable phenomenon in coastal areas. The wind, climate change, tides and  sea level rised are the triggering factors for beach erosion. Some research also shows that beach erosion influenced by the physical structure, land use changing and morphology of the beach. Ulakan Tapakis District which is geographically bordered directly with the Indian Ocean is exposed to the direct impact of beach erosion, one of the worst areas, namely Nagari Manggopoh Palak Gadang Ulakan. The annual phenomenon causes social and economic losses, also physical buildings around the coast. This study aims to examine the physical and social economic impact of beach erosion. This research was conducted by surveys and in-depth interviews with stakeholders and the data were processed by descriptive methods. The results showed that the physical impact of beach erosion, namely damaging settlement, fish auction places, towers and roads around the beach. In addition, it also causes wells shallowing and sea water intrusion. The socio-economic impact that is decreased the income of citizens up to 50% and shifting the types of livelihoods, especially in trading.